Modernización de la gestión pública y su relación con la gestión administrativa de la escuela de educación superior pedagógico público Loreto 2023 - Bajonero Castillo, Yesenia Julissa (2024)
The main objective of this study is to determine how the modernization of public management and administrative management of higher education is related to Public Pedagogical Education "Loreto", 2023. The study was basic, cross-sectional and correlational, and has a non-experimental design because the manifestations are intended in their natural state and can be studied. The sampling indicated 109 participants of this institution, in the study of the areas of management, assistant management, administration, maintenance and teaching make up the research population. Pearson's test was applied, which showed a coefficient of 0.909 indicating a significant bilateral correlation level of 0.000. This shows a strong positive relationship between the variables studied.